Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di Brawijaya Hospital Duren Tiga Jakarta Selatan - Neli Neli; Angga Juanda (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The purpose of this research is to determine the influence of compensation on employee performance at Brawijaya Duren Tiga Hospital, South Jakarta. To determine the influence of the work environment on employee performance at Brawijaya Duren Tiga Hospital, South Jakarta. To determine the influence of compensation and work environment on employee performance at Brawijaya Duren Hospital. Three South Jakarta. This research method uses a quantitative description method, data collection techniques using questionnaires. The population is 60 employees, sampling can use saturated sampling, so the sample is all 60 employees. Data analysis uses validity tests, reliability tests, classical assumption tests, multiple regression analysis, multiple correlation coefficient analysis, coefficient of determination analysis and hypothesis testing, t-test calculation results for the Compensation variable (X1) with a tcount of 9.966 and a significance of 0.000. Because tcount is smaller than ttable (9.966 > 2.002) and significance is smaller than 5% (0.050), H1 is accepted and H0 is rejected, it can be stated that Compensation (X1) has a significant effect on Employee Performance (Y). Based on the results of the Work Environment t test calculation (X2) with a tcount of 4.670 and a significance of 0.000. Because tcount is greater than ttable (4.670 < 2.002) and the significance is smaller than 5% (0.050), H2 is accepted and H0 is rejected, it can be stated that the Work Environment (X2) has a significant effect on Employee Performance (Y). Based on the results above, namely the ANOVA test, the Fcount value was 275,473, while the Ftable ( 0.05) for n = 56 was 2.77. So Fcount > from Ftable ( 0.05) or 275,473 > 2.77, with a significant level of 0.000 because 0.000 < 0.05, then it can be said that, Compensation (X1), Work Environment (X2) and together have an effect on Employee Performance (Y)